MANAJEMEN KEARSIPAN DALAM MENINGKATKAN PELAYANAN ADMINISTRASI DI SMK NEGERI 2 PANYABUNGAN - Nur Jannah; Irma Suryani Siregar; Sapirin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Archive management is the art of preparing original documents of the results of recording the results of activities carried out as a source of memory of an organization since its inception so that documents or records are easy to find when used for organizational interests such as planning, as a source of history, and as a reference for organizational decision making. Therefore, it is necessary to optimize archive management to support the achievement of effective and efficient administrative service goals. This study aims to: 1) Describe archive management at SMK Negeri 2 Panyabungan. 2) Describe administrative services at SMK Negeri 2 Panyabungan 3) Determine the supporting and inhibiting factors of archive management in improving administrative services at SMK Negeri 2 Panyabungan. This study uses qualitative research. The research procedure used produces data in the form of written words, oral expressions from sources. The informants in this study were 1 principal, 6 administrative education staff, 3 class teachers, 3 students. Data Primary data obtained from the results of interviews with observations. Secondary data, obtained through literature studies, references, and documentation obtained from the research location. The results of the study indicate that 1). Archives management in improving administrative services at SMK Negeri 2 Panyabungan is said to be good according to the results of research at the planning stage to the evaluation of good archives management. 2). Administrative services at SMK N 2 Panyabungan show effective and efficient results, seen in terms of the implementation of archives management that is in accordance with the needs and conditions of the school. 3). Supporting and inhibiting factors for archives management in improving administrative services at SMK Negeri 2 Panyabungan are the existence of supporting facilities and infrastructure, expert competence in archives management to improve administrative services at SMK Negeri 2 Panyabungan, This is also proven by modern archive management and relevant archive indexing so as to facilitate the retrieval of archives when needed in administrative services.